FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Rike Yolanda Panjaitan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2021)
This research aims to find out the influence of free cash flow, managerial ownership and institutional ownership on debt policy with the size of the company as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. The variables used in the study were free cash flow, managerial ownership and institutional ownership as independent variables, debt policy as dependent variables and investment opportunity sets as moderating variables. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. The study was conducted on 24 companies that met the sampling criteria of 171 manufacturing companies listed on the Indonesia Stock Exchange. The research data is secondary data in the form of annual financial statements of 24 companies published on the Indonesia Stock Exchange. The data processing method in this study used multiple linear regression tests, moderating tests that used residual tests. By first testing on classical assumptions. The results showed that (1) free cash flow has a significant effect on debt policy variables, (2) managerial ownership has unsignificant effect on debt policy variables, (3) institutional ownership has a significant effect on debt policy variables (4) free cash flow, managerial ownership and institutional ownership simultaneously affects debt policy, (5) investment opportunity set is able to moderate the relationship between free cash flow to debt policy, (6) investment opportunity set is able to moderate the relationship between asset structure to debt policy, (7) investment opportunity set is able to moderate the relationship between profitability to debt policy.